Layanan Konseling Kesehatan Untuk Meningkatkan Psychological Well Being Mahasiswa - Lucia Hernawati (Universitas Katolik Soegijapranata, 2019)
University is not only a place where students get knowledge academically but also non-academically. It must show responsibility to give students the opportunity to have a good life. For this reason, university must help students to be aware of their self, their purpose in life and passion. It must help students develop their potential so they can live happily (well being especially psychological well being). The life satisfaction and happiness (psychological well being) can be fulfilled if the individual is in good health. The World Health Organization defines health as being physically, mentally and socially healthy. Health counseling can help individualsoptimize their potential. Continuous efforts to maintain body fitness, manage emotion and thinking ability for giving positive interpretation in life experinces and harmony social interaction and mutual support to others make individuals feel satisfied in life and happy. The purpose of this activity is to provide health counseling services to increase students' psychological well being. Thirty students from various faculties at UnikaSoegijapranata were involved in this activity. By attending three health counseling sessions with the theme of physical, mental, and social health there was an increase in psychological well being.